Quasi-option value under strategic interactions - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2013)
We consider a simple two-period model of irreversible investment under strategic interactions between two players. In this setup, we show that the quasi-option value may cause some conceptual difficulties. In case of asymmetric information, decentralized investment decisions fail to induce first-best allocations. Therefore a regulator may not be able to exercise the option to delay the decision to develop. We also show that information-induced inefficiency may arise in a game situation and that under certain assumptions inefficiency can be eliminated by sending asymmetric information to the players, even when the regulator faces informational constraints. Our model is potentially applicable to various global environmental problems.